2021
DOI: 10.1016/j.lanepe.2021.100097
|View full text |Cite
|
Sign up to set email alerts
|

Underlying conditions and risk of hospitalisation, ICU admission and mortality among those with COVID-19 in Ireland: A national surveillance study

Abstract: Background To date, over 2 million people worldwide have died with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. To describe the experience in Ireland, this study examined associations between underlying conditions and the following outcomes: mortality, admission to hospital or admission to the intensive care unit (ICU) among those infected with COVID-19. Methods This study used data from the Health Protection Surveillance Centre in Ireland and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
27
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 20 publications
9
27
4
1
Order By: Relevance
“… 3 Nevertheless, several underlying diseases, such as cancer, hypertension, and cardiovascular diseases, act as risk factors for severe COVID-19 or COVID-19-related mortality. 2 12 32 In COVID-19 patients with cancer, systemic immunosuppression associated with the cancer itself or anticancer therapy might affect the vulnerability to severe COVID-19 or COVID-19-related mortality, which is consistent with our findings. Diabetes, known to be a hazardous comorbidity in fatal COVID-19 cases, was also associated with COVID-19-related mortality in the present study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“… 3 Nevertheless, several underlying diseases, such as cancer, hypertension, and cardiovascular diseases, act as risk factors for severe COVID-19 or COVID-19-related mortality. 2 12 32 In COVID-19 patients with cancer, systemic immunosuppression associated with the cancer itself or anticancer therapy might affect the vulnerability to severe COVID-19 or COVID-19-related mortality, which is consistent with our findings. Diabetes, known to be a hazardous comorbidity in fatal COVID-19 cases, was also associated with COVID-19-related mortality in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies on the estimation of severity and mortality of COVID-19 showed diverse results, with the identification of a limited number of predictors, such as age and sex. 6 7 8 9 10 Age and underlying diseases are known factors associated with higher risks of mortality in patients with COVID-19, 2 6 7 11 12 which is partially related with increased severity and susceptibility to COVID-19. 13 14 However, heterogeneity in age and underlying diseases could affect COVID-19-related mortality, and therefore, findings from previous studies were inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming that 10% of patients diagnosed with COVID-19 will be admitted to hospital [ 6 ], a 0.05 acceptable difference in apparent and adjusted Cox-Snell R-squared, 0.05 margin of error in estimation of the intercept, a binary outcome based on admission to hospital, and a maximum of 24 predictor parameters [ 5 ], we estimate that the minimum sample size required for new model development is 1317 participants enrolled for the development set [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…Neurotropic nature of SARS-CoV-2 predetermines psychiatric disorders in some patients with COVID-19 [1][2][3]. However, most publications on the psychological and mental impact of COVID-19 present the results of online and cross-sectional studies of the general population [4][5][6][7] or post-recovery data of patients who have suffered the acuteSARS-CoV-2 infection earlier [8][9][10][11]. Even the clinical findings from previous coronavirus crises are mostly symptom-and dimension-oriented.…”
Section: Introductionmentioning
confidence: 99%